Currency interventions: Effective policy tool or shortsighted gamble? - Keith Pilbeam; Arturo Bris; Cinzia Alcidi; Mikkel Barslund; Willem Pieter De Groen; Daniel Gros (Intereconomics, 2015)
The Swiss National Bank's January 2015 decision to abandon the Swiss franc's peg to the euro led to short-term chaos in exchange markets and had a dampening effect on the Swiss economy. Some economists suggested Switzerland was poised to enter a sustained period of stagnation à la Japan. The decision also reignited policy debate on the benefi ts and drawbacks to central bank intervention in currency markets. While such intervention can be justifi ed in certain situations, such as if the market is producing the 'wrong rate', it can also impose signifi cant economic costs. The ECB's recently implemented quantitative easing programme has been regarded by many as a thinly disguised attempt to weaken the euro in order to improve the eurozone's competitiveness. However, the euro's recent weakening began well before the ECB announced its programme; moreover, previous rounds of quantitative easing by other central banks have had minimal impact on exchange rates.
Keywords: 330; Devisenmarkt; Geldpolitik; Eurozone